2014
DOI: 10.25103/jestr.073.17
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Performance of MIMO systems for Wireless Communications

Abstract: This paper presents the capacity performance of multiple antennas for wireless communication systems. Multiple antennas structures can be classified into single-input multiple-outputs (SIMO), multiple-inputs single output (MISO), and multiple-inputs multiple-outputs (MIMO) systems. Assuming that the channel is unknown at receiver, capacity expressions are provided for each structure. Our results also show that increasing the number of transmitting and receiving antennas for a wireless MIMO channel does indeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It can be observed that the channel capacity of the proposed MIMO antenna is higher than SISO configuration under similar conditions. Considering SNR = 20 dB, the proposed antenna has channel capacity of 19.9 which is almost three times higher than the SISO configuration of ≈5.89 bps/Hz [32]. Hence, this antenna is a promising candidate for high-data-rate head implants.…”
Section: A Mimo Channel Parametersmentioning
confidence: 98%
“…It can be observed that the channel capacity of the proposed MIMO antenna is higher than SISO configuration under similar conditions. Considering SNR = 20 dB, the proposed antenna has channel capacity of 19.9 which is almost three times higher than the SISO configuration of ≈5.89 bps/Hz [32]. Hence, this antenna is a promising candidate for high-data-rate head implants.…”
Section: A Mimo Channel Parametersmentioning
confidence: 98%
“…In the continuing evolution of antenna array-based transmission systems, MIMO systems are emerging. These multi-antenna systems represent a combination of several transmit and receive antennas 11 , which allows to increase: the transmit and receive diversity, the capacity of the system, and the transmission rates.…”
Section: System Descriptionmentioning
confidence: 99%
“…Example of block diagram of a (N t x N r ) transmission MIMO system Now, let x i be the input data and y j the output data; it is assumed that noise can affect the transmission and, therefore, b j is considered to be white Gaussian noise of zero mean. Then, the output (y j ) of the system is 11 :…”
Section: Figurementioning
confidence: 99%
“…In a digital communication system, capacity is used as performance measure. It is the maximum transmission rate of which communication can be achieved [4]. The channel capacity of a SISO system is given by the equation below [5].…”
Section: Introductionmentioning
confidence: 99%
“…4 lists antenna parameters at different values of the inset notch width. Where Gf=0.0837 is the calculated value obtained from equation (6.6).…”
mentioning
confidence: 99%